Did militancy help or hinder the granting of women's suffrage in Britain?. Issue 7 (10th November 2019) - Purvis, June
ABSTRACT: This Viewpoint is one of three discussing the question of whether the 'militant' tactics of the suffragettes, as member of the Women's Social and Political Union (WSPU) were called in Edwardian Britain, helped or hindered the granting of women's suffrage. In this contribution, it is suggested that militancy embraced a broad range of behaviours, both legal and illegal, that were central to the WSPU campaign and to the granting of the parliamentary vote.